Microbial Interspecies Associations in Fracture-Related Infection. Issue 6 (June 2022) - Gitajn, Ida; Werth, Paul; O'Toole, Robert V.; Joshi, Mandarin; Jevsevar, David; Wise, Brent; Rane, Ajinya; Horton, Steven; McClure, Emily A.; Ross, Benjamin; Nadell, Carey
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: Describe co-occurrence or clustering of microbial taxa in fracture-related infections to inform further exploration of infection-related interactions among them. Design: Retrospective review. Setting: Level 1 trauma center. Patients/Participants: Four hundred twenty-three patients requiring surgical intervention for deep surgical site infection between January 2006 and December 2015. Intervention: None. Main Outcome Measurement: Connection between microbial taxa. Results: Methicillin-resistant Staphylococcus aureus, methicillin-sensitive Staphylococcus aureus, and coagulase-negative Staphylococcus represented the majority of monomicrobial observations (71%). Gram-negative rods, gram-positive rods, and anaerobes presented more frequently in polymicrobial infections. Enterobacter, vancomycin-sensitive Enterococcus, and Pseudomonas are present in polymicrobial infections with the highest frequencies and represent the top 3 most important nodes within the microorganism framework, with the highest network centrality scores. Conclusions: The present study indicates that there are common microbial taxa ( Enterobacter, Enterococcus, and Pseudomonas ) that tend to co-occur with other microbes greater than 75% of the time. These commonly co-occurring microbes have demonstrated interactive relationships in other disease pathologies, suggesting that there may be similar important interactions in fracture-related infections. It is possible that these microbial communities play a role in the persistently high failure rate associated with management of infection after trauma. Future studies are needed to study the intermicrobial interactions that explain the frequency at which taxa co-occur. Understanding and potentially disrupting these intermicrobial relationships could inform improvements in the treatment of established infections and in the prevention of infection in high-risk patients. Level of Evidence: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.